Article Penerapan Media “BICOLA” Untuk Meningkatkan Pemahaman Konsep Materi Perkalian Peserta Didik Kelas 2 - Lisda Arnima Meiyanti; Zuliana, Eka; Vebriani, Niasari (FKIP Universitas Mataram, 2025)
One of the crucial basic knowledge is mathematics, which not only continues to develop but also underlies technological progress and human thinking. Although important, mathematics learning, especially at the elementary school level, is often hampered by the abstract nature of its concepts, especially for students who need a concrete understanding of concepts.This research aims to determine the increase in conceptual understanding of class II students at SDN Jati Wetan 2 through the application of BICOLA (Congklak Bianglala) media in multiplication material. This research is Classroom Action Research. The data collection stage in this classroom action research is two cycles consisting of 3 meetings in each cycle. Each cycle consists of (1) Planning; (2) Implementation; (3) Observation; and (4) Reflection. Data collection techniques through observation, tests and documentation. Data analysis uses qualitative and quantitative descriptive. The results of this research show that there is an increase in students' understanding of the concept of multiplication material. Comparison of the percentage of achievement of completeness, initially only 4 students were able to achieve a score > 75 in the first cycle, and increased to 10 students in the second cycle from 12 students in the class. The average learning test results also increased, from 56.2 in the pretest to 62.9 in the first cycle, and increased to 83.3 in the second cycle. The level of students' understanding of concepts increased from the first cycle by 70.66 to 80.66 in the second cycle. The application of BICOLA media has been proven to increase students' understanding of concepts and activeness in multiplication material in class 2 of SDN Jati Wetan 2.